An introduction to microcomputer systems: Architecture and interfacing - Fulcher, John (Addison - Wesley Publishing Company, 1989)
This book provides a thoroughly modern and up-to-date introduction to microcomputer interfacing, as well as a general introuduction to the fundamentals of microcomputer architecture.